Smart grid: Interoperability and cyber security - Gündüz, Muhammed Zekeriya; Daş, Resul (Elsevier, 2024)
Interoperability and cyber security, guided by established standards, play crucial roles in providing efficient and secure operations for smart grid applications. Interoperability enables seamless communication and coordination among various devices, systems, and stakeholders in the smart grid ecosystem, while cyber security protects against potential threats and vulnerabilities. This chapter examines the interoperability and cyber security in smart grids, with a specific focus on the role of standards. It examines the significance of standardized protocols and interfaces enabling interoperability and facilitating the integration of devices and technologies. Moreover, the chapter analyzes the existing standards and frameworks in the field, such as NERC, NIST, and Federal Energy Regulatory Commission standards, and their contributions to addressing interoperability and cyber security challenges. By analyzing these standards, this chapter aims to contribute to a better understanding of the importance of interoperability and cyber security in smart grid system and the role of regulatory bodies and standards organizations in guiding the industry toward a more resilient and secure electric power system. © 2025 Elsevier Inc. All rights reserved.
Keywords: Cyber security; Interoperability; Smart grid; Smart grid applications